Pengaruh Displin Kerja Terhadap Kinerja Pegawai pada Dinas Komunikasi dan Informatika (Diskominfo) Kabupaten Purwakarta - Deddy Dariansyah; Noviariany Noviariany; Syahid Syahid (Universitas Indraprasta PGRI, 2020)
This study aims to analyze the effect of work discipline on the performance of the employees of the Office of Communication and Information in Purwakrta Regency. Field method with regression statistical analysis approach. By using the method and these variables are expected to solve problems that occur in employees in the Office of Communication and Information Purwakarta Regency. The respondents in this study were 50 employees. The results of the analysis show that work discipline has a positive effect on employee performance in the moderate influence category. This can be seen from the statistical results of the correlation test and hypothesis testing of the two variables using the multiple linear F tests and the T-test, while the statistical test for the Work Discipline variable is positively and significantly affected by employee performance. Thus, these empirical findings indicate that to improve employee performance it is necessary to improve service quality and improve discipline levels